TSemantic domain and reading comprehension in students of the Faculty of Education at the Universidad Nacional Federico Villarreal, Lima – Peru - Núñez Montalvan, Karina Cecilia (2017)
The purpose of this paper is to demonstrate the relation between the semantic command andreading comprehension in students from the Education Faculty of Universidad Nacional FedericoVillarreal from Lima. The research done on a sample of 70 people to whom two instrumentswere provided: a questionnaire that measures the semantic command (Nuñez, 2012) in thefollowing fields: vocabulary in context (nouns, adjectives and verbs); synonyms in context (nouns,adjectives and verbs); antonyms (nouns, adjectives and verbs); paronyms (nouns, adjectivesand verbs); homonyms (nouns, adjectives and verbs); hyperonyms and hyponyms (nouns andverbs); linkers (conjunctions and connectors). It is valid and reliable in 0,891 and there is also areading comprehension test (Tapia, 2012). It consists of 10 pieces of reading, divided in threedimensions: Literal (Information about facts, definition of meanings); Inferential (Identification of the main idea, understanding of facts, inference about the author, inference about the content ofthe pieces of reading, mark or give a title to the text); Criterial (assessment of the facts presentedin the texts), it has reliability of 0,66. Results report the existence of a meaningful relation of0,693 between the semantic domain and reading comprehension among students. Regardingdimensions, it is observed an average relation (0,453) between the semantic domain and readingcomprehension in the Literal level; a weak relation (0,276) between the semantic domain andreading comprehension in the Inferential level; and, a low relation (0,369) between the semanticdomain and criterial comprehension.